A screening study of drug-drug interactions in cerivastatin users: an adverse effect of clopidogrel. - Floyd, J S; Kaspera, R; Marciante, K D; Weiss, N S; Heckbert, S R; Lumley, T; Wiggins, K L; Tamraz, B; Kwok, P-Y; Totah, R A; Psaty, B M (Clin Pharmacol Ther, 2012)
An analysis of a case-control study of rhabdomyolysis was conducted to screen for previously unrecognized cytochrome P450 enzyme (CYP) 2C8 inhibitors that may cause other clinically important drug-drug interactions. Medication use in cases of rhabdomyolysis using cerivastatin (n = 72) was compared with that in controls using atorvastatin (n = 287) for the period 1998-2001. The use of clopidogrel was strongly associated with rhabdomyolysis (odds ratio (OR) 29.6; 95% confidence interval (CI), 6.1-143). In a replication effort that used the US Food and Drug Administration (FDA) Adverse Event Reporting System (AERS), it was found that clopidogrel was used more commonly in patients with rhabdomyolysis receiving cerivastatin (17%) than in those receiving atorvastatin (0%, OR infinity; 95% CI = 5.2-infinity). Several medications were tested in vitro for their potential to cause drug-drug interactions. Clopidogrel, rosiglitazone, and montelukast were the most potent inhibitors of cerivastatin metabolism. Clopidogrel and its metabolites also inhibited cerivastatin metabolism in human hepatocytes. These epidemiological and in vitro findings suggest that clopidogrel may cause clinically important, dose-dependent drug-drug interactions with other medications metabolized by CYP2C8.
Keywords: Adverse Drug Reaction Reporting Systems; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Cytochrome P-450 CYP3A; Cytochrome P-450 CYP3A Inhibitors; Drug Interactions; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Platelet Aggregation Inhibitors; Pyridines; Rhabdomyolysis; Ticlopidine